Land use efficiency on example of the transformation of rural properties - Jasińska, Elżbieta (International Conference “Environmental Engineering”, 2017)
Appropriate use of the economic potential of the property is a challenge not only for planners and local authorities, it is also important for the individual owners. The biggest changes will result from changes in local planning, mainly from the conversion of agricultural land for residential purposes. However, legislative changes were created to protect this type of land against uncontrolled rotation. The changes made in recent years, complicated, or even impossible so far used the process of buying and subsequent conversion of the property, to the needs of the real estate market premises or services. The article presents the ideas of Land Use Efficiency on the example of transformation of agricultural real estate in the property held for development. Example simulations are an empirical transformation or division of property to sell them for housing purposes. These examples illustrated in the example of land developing, for whom the lack of local development plans or plans are developed recently. For this purpose, a qualitative and quantitative approaches, including decision trees to determine the criteria for the formation of real estate prices. The author draws attention to the possibility of the development of non-urbanized areas and the potential costs and financial returns resulting therefrom.